Simulation on Vortex Induced Vibration of Circular Cylinder. (April 2020) - Chang, T J; Lua, K B
Abstract: In order to study the vortical flow field and the vibration caused by fluid-structure interaction (FSI), an efficient simulation setup was established. The simulation made use of the built-in Deforming Mesh function, Semi-Implicit Method for Pressure Linked Equations (SIMPLE) Algorithm and SST-kw Turbulence Model of Ansys Fluent to generate the flow field. A User Defined Function (UDF) was written to calculate the displacement of the cylinder based on the simulated flow field information. A range of Reduced Velocity was scanned through in order to find the "locked-in" region, which is the resonance occurring region. The present study focused on the forces acting on the cylinder and the resultant trajectory of different cylinder natural frequencies. The simulation needs further fine tuning to improve the accuracy.